Separate and Sacred: A Ritual Critique of Gothic Revival Architecture - Strout, Shawn O. (Studia liturgica, 2026)
Gothic Revival architecture has had an outsized impact on churches since the nineteenth century. While it originated in the Church of England, it has spread to many other parts of the globe and among other ecclesial traditions, including those without prescribed liturgical forms. Theories for the popularity of this architectural style include its appeal to romanticism, nationalism/colonialism, and the desire for Christian unity. These theories offer sociological factors involved in its perdurance but fail to explain its more profound influence. Ritual theory, with its understanding of sacred space, liminality, and ritualization, offers insights into these more profound influences.